THEORETICAL FOUNDATIONS OF STRATEGIC MANAGEMENT IN THE BUILDING MATERIALS INDUSTRY (Marketing Journal, 2025)
This article analyzes the theoretical foundations of strategic management in the construction materials industry. It focuses on key concepts, principles, and models of strategic management, as well as the specific characteristics of the construction materi als sector. The analysis of literature, existing methodologies, and findings highlights tools that support strategic decision -making. The article also discusses 400 challenges and promising directions for implementing strategic management in this industry. The conclusion summarizes the main findings.
Keywords: strategic management; construction materials industry; competitive environment; SWOT analysis; PEST analysis; portfolio analysis; strategic planning; competitive strategies; innovation; sustainability; risk management